Tetrahydrocannabinol-Rich Extracts From Cannabis Sativa L. Improve Glucose Consumption and Modulate Metabolic Complications Linked to Neurodegenerative Diseases in Isolated Rat Brains - Erukainure, Ochuko L.; Matsabisa, Motlalepula G.; Salau, Veronica F.; Islam, Md. Shahidul (Frontiers in Pharmacology, 2020)
Reduced brain glucose consumption arising from impaired glucose uptake and utilization has been linked to the pathogenesis and complications of neurodegenerative diseases. The ability of Cannabis sativa L. tetrahydrocannabinol-rich extracts to stimulate brain glucose uptake and utilization as well as its modulatory effect on gluconeogenesis, antioxidative, purinergic and cholinergic activities were investigated in isolated rats’ brains. C. sativa leaves were sequentially extracted to yield the hexane and dichloromethane (DCM) extracts. The extracts were incubated at 37˚C with freshly harvested brains in the presence of glucose for 2h. The control consisted of incubation without the extracts, while brains without the extracts and glucose served as the normal control. Metformin was used as the standard drug. C. sativa extracts caused a significant (p<0.05) increase in brain glucose uptake, with concomitant elevation of glutathione level, superoxide dismutase, catalase, and ecto-nucleoside triphosphate diphosphohydrolase activities compared to the controls. Incubation with C. sativa extracts also led to depletion in malondialdehyde and nitric oxide levels, acetylcholinesterase, butyrylcholinesterase, glucose 6-phosphatase and fructose-1,6-biphosphatase activities. GC-MS analysis of the extracts revealed the presence of tetrahydrocannabinol. In silico analysis predicted tetrahydrocannabinol to be permeable across the blood-brain-barrier. Tetrahydrocannabinol was also predicted to have an oral LD50 and toxicity class values of 482 mg/kg and 4 respectively. These results indicate that C. sativa improves glucose consumption with concomitant suppression of oxidative stress and cholinergic dysfunction, and modulation of purinergic and gluconeogenic activities in brain tissues